Optimum Risk-Based Management on the Lhokseumawe City Ring Road which is Vulnerable to Coastal Abrasion - Ridwan, Teuku Muhammad; Amri, Amri; Syahrial, Syahrial; Ayob, A F (Malikussaleh University, Aceh, Indonesia, 2022)
The city of Lhokseumawe, which is one of the cities that has a topography such as a bay and a very busy area as the center of government, business, and services, has also experienced congestion. In 2012, the Lhokseumawe City Government has started planning to build a 7.6 Kilometer Lhokseumawe City Ring Road, starting from Sp.Kandang – Pusong and Sp. Lestari – Loskala. The ring road construction is along the shores of Ujong Blang Beach and KP3, where Ujong Blang Beach and KP3 since 1998 until now continue to experience abrasion. The purpose of this study was to determine the level of abrasion speed of Ujong Blang Beach and KP3 Beach and risk factors other than abrasion for an optimal risk-based management model approach to the Lhokseumawe City Ring Road as coastal infrastructure that is prone to abrasion and other risks. The method used to determine the abrasion rate is based on Landsat ETM+ (Enhanced Thematic Mapper) satellite data for a period of 25 years (1995 – 2020) which is analyzed by the Digital Shoreline Analysis System. The results showed that the magnitude of the abrasion speed of Ujong Blang Beach and KP3 Beach was -2.11 m/year and the farthest accretion occurred on the coast on transect 83 with an accretion distance of 111.34 m or around 4.45. Meanwhile, other factors were sea waves. with a period range of 2.33-10.25 s with an average of 4.57 s. Furthermore, the height of the coastal topography ranges from 0.00-8.60 m with an average of 4.30 m and the coastal slope observed at 8 observation locations obtained a coastal slope range of 2.90-4.47% with an average slope of 3,76%. The optimum risk-based management carried out by the ring road manager is the ALARP-principles approach to control very high to high risk (ALARP Zone), namely by building a preventive building in the form of a conventional type of breakwater with minimal handling costs to mitigate a greater impact on the environment. Damage to the Lhokseumawe City Ring Road if the risk occurs during the life of the road plan.